(untitled) (Journal of the College of Basic Education, 2023)
The research aims to identify (the effect of the Klosemeyer and Merrill-Tenson models on academic achievement in biology for second grade intermediate female students). The researchers chose the Arab Heritage School from among the schools affiliated to the General Directorate of Education of Karkh / Al-Oula in the city of Baghdad. In a number of variables (chronological age, testing previous information, previous academic achievement, and parental educational attainment). The researchers formulated (79) behavioral objectives for the content of the subjects according to Bloom’s taxonomy in the cognitive field (remember, understand, apply). Educational plans were prepared The topics that you will study during the experiment were presented to a group of experts and arbitrators in the methods of teaching science. The researchers prepared an achievement test (post-test) consisting of (63) items and it was of the type of multiple choice. Its apparent validity, content validity and stability reached (0.934).The researchers used the following statistical methods in their research procedures and analysis of the results: (One-way analysis of variance, the Chi test, the difficulty coefficient equation, Pearson correlation coefficient, Spearman-Brown coefficient, and the Scheffie test) and the results that were reached:The students of the first experimental group who studied according to the Klosemeyer model and the students of the second experimental group who studied according to the Merle-Tenson model outperformed the students of the control group who studied according to the traditional method. The first experimental group who studied according to the Klosemeyer model is equal to the second experimental group who studied according to the Merle-Tenson model. In the light of the research results, the researchers recommended emphasizing the use of the Klosemeyer and Merle-Tenson educational models in learning biological concepts for secondary school students. Male and female teachers on how to learn biological concepts according to the two educational models (Klausmeyer and Merle-Tenson) and conducting a study similar to the current study by using other educational models such as the Janier, Bruner and Hilida Tapa educational models.